Is iatrogenic sleep disturbance worth the effort in Type 1 diabetes?. Issue 8 (15th July 2015) - Barnard, K. D.; Oliver, N.; Adolfsson, P.; Aldred, C.; Kerr, D.
What's new? Chronic sleep disturbance is common for people with Type 1 diabetes. Fear of nocturnal hypoglycaemia is causing frequent nocturnal blood glucose testing causing impaired sleep. New strategies for the prevention of nocturnal hypoglycaemia need to be devised and tested. The consequences of chronic sleep disturbance for people living with diabetes and their families needs to be appreciated by their clinical advisors.